Higher-Institution-Based Film Festivals as a Vehicle to Improve Student Production Quality and Form University–Industry Connections - Liu, Yong; Ling, Mayyer; Nechita, Florin (MDPI AG, 2023)
This paper will be focusing on discussions on how to use small-scale, higher-institution-based film festivals (including film competitions) as a vehicle to motivate students who are majoring in media and screen production to improve their production quality for both module assignments and competition-targeted special projects. Moreover, this paper will argue that, by inviting industry representatives to be involved in judging and commenting on student works, such small-scale film festivals organised by higher education institutions over time may grow into a platform that not only recognises and supports budding directors, screenwriters, actors, and actresses in Brunei but also acts as a playing field in which novice filmmakers can connect with experts, exchange ideas, acquire valuable skills, and enable further collaboration in the future. Based on first-hand data collection, an analysis, and semi-structured interviews of the multiple parties involved, our discussions cover how to launch the production process for screen-practice-based education, how to organise module assignments to fit the themes of specific film festivals/competitions, and how to overcome the challenges facing students working in a multicultural production team, etc. Two higher-institution-based film festivals, i.e., PRISM UBD Short Film Festival organised by Universiti Brunei Darussalam and the Dracula Digital competition, a mobile-phone filmmaking competition run by Transilvania University of Brasov, Romania, are used as analytical case studies.
Keywords: higher education; film festivals; learning experience; university-industry connections